PERAN PEMBIMBING KEMASYARAKATAN DALAM PROGRAM REINTEGRASI EKS NARAPIDANA TERORIS - Abdul Hijar Anwar (Ensiklopedia Social Review, 2025)
Abstract: In social reintegration there are micro interventions. Micro intervention is a community guidance skill in overcoming problems faced by individuals and families. Micro intervention (Social Casework) is a therapy that is carried out face to face, namely a social guide with the client. This is done to reveal or explore fundamental problems so that they can help in the service process. Apart from that, it is also carried out to find a solution to solve problems related to the problems being faced by clients. The field of social work covers social problems that occur in individuals, groups and society.Keywords: Community Guidance, Reintegration, Terrorist Convicts.